Hydrogen: Safety, Storage, and Transportation, Perspectives, and Measures - Mubbashar Mehmood; Ali O. M. Maka (Advanced Energy Conversion Materials, 2025)
Reducing greenhouse gas emissions is a target for many industries to achieve the United Nations Sustainable Development Goals’ energy objectives and to reach Net Zero. Hydrogen has been identified as a potential energy carrier with almost zero emissions. However, there are challenges in safety during the storage and transportation of hydrogen. This paper provides an insight into various storage technologies and transportation methods, along with their limitations and potential applications. Highly compressed hydrogen requires high-pressure storage tanks that necessitate special materials and enhanced safety measures to prevent leakage or explosion. Liquid hydrogen requires cryogenic temperatures (-253.0 °C) and requires super-insulated tanks to minimise heat loss and reduce the boil-off ratio. Currently, the most viable solution for storing hydrogen safely is the absorption process, which utilizes Metal Hydride (MH) tanks. In addition to transporting hydrogen using tanks and cylinders, it can also be transported via pipelines. API X65 material can be used to transport hydrogen in the subsea. However, more research is required on the material for safely storing hydrogen in cylinders and innovative sensors to detect any leakage immediately.